Improving heat aging and mechanical properties of fluoroelastomer using carbon nanotubes - Heidarian, J.; Hassan, A. (De Gruyter Open, 2017)
Carbon nanotube (CNT)-, carbon black (CB)-filled fluoroelastomer (FE) and unfilled-FE compounds were prepared (CNT/FE, CB/FE and FE). The compounds were subjected to heat air aging and characterized by tensile test and X-Ray Diffraction (XRD) analysis. Results show that CNT improved tensile properties of FE before and after aging. All samples show stress induced crystallization (SIC) during tension. XRD results show that under all conditions, the crystals were in the form of γ-phase. For both aged and un-aged specimens, the degree of crystallinity (Xc) is low. After tensile stretching, Xc of un-aged specimens increases tremendously, with larger crystal size. Under the same conditions, the order of elongation at break (EL) was FE > CB/FE > CNT/FE. Normal modulus (NM) and tangent modulus (TM) at the same conditions was in the order of CNT/FE > CB/FE > FE. Tensile strength had the order of CNT/FE > CB/FE > FE.